Quantitative cerebrovascular reactivity MRI in mice using acetazolamide challenge. Issue 5 (17th June 2022) - Wei, Zhiliang; Li, Yuguo; Hou, Xirui; Han, Zheng; Xu, Jiadi; McMahon, Michael T.; Duan, Wenzhen; Liu, Guanshu; Lu, Hanzhang
Abstract : Purpose: To develop a quantitative MRI method to estimate cerebrovascular reactivity (CVR) in mice. Methods: We described an MRI procedure to measure cerebral vasodilatory response to acetazolamide (ACZ), a vasoactive agent previously used in human clinical imaging. Vascular response was determined by cerebral blood flow (CBF) measured with phase‐contrast or pseudo‐continuous arterial spin labeling MRI. Vasodilatory input intensity was determined by plasma ACZ level using high‐performance liquid chromatography. We verified the source of the CVR MRI signal by comparing ACZ injection to phosphate‐buffered saline injection and noninjection experiments. Dose dependence and feasibility of regional CVR measurement were also investigated. Results: Cerebral blood flow revealed an exponential increase following intravenous ACZ injection, with a time constant of 1.62 min. In contrast, phosphate‐buffered saline or noninjection exhibited a slow linear CBF increase, consistent with a gradual accumulation of anesthetic agent, isoflurane, used in this study. When comparing different ACZ doses, injections of 30, 60, 120, and 180 mg/kg yielded a linear increase in plasma ACZ concentration ( p < 0.0001). On the other hand, CBF changes under these doses were not different from each other ( p = 0.50). The pseudo‐continuous arterial spin labeling MRI with multiple postlabeling delays revealed similar vascular responses at different postlabeling delay values. There was a regional difference in CVR ( p = 0.005), with isocortex (0.81 ± 0.17%/[μg/ml]) showing higher CVR than deep‐brain regions. Mice receiving multiple ACZ injections lived for a minimum of 6 months after the study without noticeable aberrant behavior or appearance. Conclusions: We demonstrated the proof‐of‐principle of a new quantitative CVR mapping technique in mice.